Improvement of PHBV Scaffolds with Bioglass for Cartilage Tissue Engineering - Wu, Jun; Xue, Ke; Li, Haiyan; Sun, Junying; Liu, Kai (PLOS ONE, 2013)
Polymer scaffold systems consisting of poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) have proven to be possible matrices for the three-dimensional growth of chondrocyte cultures. However, the engineered cartilage grown on these PHBV scaffolds is currently unsatisfactory for clinical applications due to PHBV’s poor hydrophilicity, resulting in inadequate thickness and poor biomechanical properties of the engineered cartilage. It has been reported that the incorporation of Bioglass (BG) into PHBV can improve the hydrophilicity of the composites. In this study, we compared the effects of PHBV scaffolds and PHBV/BG composite scaffolds on the properties of engineered cartilage in vivo. Rabbit articular chondrocytes were seeded into PHBV scaffolds and PHBV/BG scaffolds. Short-term in vitro culture followed by long-term in vivo transplantation was performed to evaluate the difference in cartilage regeneration between the cartilage layers grown on PHBV and PHBV/BG scaffolds. The results show that the incorporation of BG into PHBV efficiently improved both the hydrophilicity of the composites and the percentage of adhered cells and promoted cell migration into the inner part the constructs. With prolonged incubation time in vivo, the chondrocyte-scaffold constructs in the PHBV/BG group formed thicker cartilage-like tissue with better biomechanical properties and a higher cartilage matrix content than the constructs in the PHBV/BG group. These results indicate that PHBV/BG scaffolds can be used to prepare better engineered cartilage than pure PHBV.